Differences in Physiological and Perceptual Responses to High Intensity Interval Exercise Between Arm and Leg Cycling - Astorino, Todd A.; Emma, Danielle (Frontiers in Physiology, 2021)
This study compared changes in oxygen uptake (VO2), heart rate (HR), blood lactate concentration (BLa), affective valence, and rating of perceived exertion (RPE) between sessions of high intensity interval exercise (HIIE) performed on the arm (ACE) and leg cycle ergometer (LCE). Twenty three active and non-obese men and women (age and BMI = 24.7 ± 5.8 yr and 24.8 ± 3.4 kg/m2) initially underwent graded exercise testing to determine VO2max and peak power output (PPO) on both ergometers. Subsequently on two separate days, they performed ten 1 minute intervals of ACE or LCE at 75 %PPO separated by 1 min of active recovery at 10 %PPO. Gas exchange data, HR, and perceptual responses were obtained continuously and blood samples were acquired pre- and post-exercise to assess the change in BLa. VO2max and PPO on the LCE were significantly higher (p < 0.001) than ACE (37.2 ± 6.3 mL/kg/min vs. 26.3 ± 6.6 mL/kg/min and 259.0 ± 48.0 W vs. 120.0 ± 48.1 W). Mean VO2 (1.7 ± 0.3 L/min vs. 1.1 ± 0.3 L/min, d = 2.3) and HR (149 ± 14 b/min vs. 131 ± 17 b/min, d = 2.1) were higher (p < 0.001) in response to LCE versus ACE as was BLa (7.6 ± 2.6 mM vs. 5.3 ± 2.5 mM, d = 2.3), yet there was no difference (p = 0.12) in peak VO2/HR. Leg cycling elicited higher relative HR compared to ACE (81 ± 5 vs. 75 ± 7 %HRmax, p = 0.01) although there was no difference in relative VO2 (63 ± 6 vs. 60 ± 8 %VO2max, p = 0.09) between modes. Affective valence was lower during LCE versus ACE (p = 0.003), although no differences in enjoyment (p = 0.68) or RPE (p = 0.59) were demonstrated. Overall, HIIE performed on the cycle ergometer elicits higher relative oxygen uptake and blood lactate concentration and a more aversive affective valence, making these modes not interchangeable in terms of the acute physiological and perceptual response to interval based exercise.